PENGARUH SUPLEMENTASI SILASE CAMPURAN SORGHUM- Clitoria ternatea PADA BERBAGAI LEVEL KONSENTRAT MENGANDUNG ZnSO4 DAN Zn-Cu ISOLEUSINAT TERHADAP FERMENTASI RUMEN KAMBING KACANG (Effects of supplemented mixed silage of sorghum-clitoria ternatea with.....) - Adrianus Safarius Radja; Markus M. Kleden; Gusti A. Y. Lestari (JURNAL NUKLEUS PETERNAKAN, 2020)
The purpose of this study was to determine the effect ofsupplemented mixed silage of sorghum-Clitoriaternatea with different levels of concentrate containing ZnSO4 and Zn-Cu Isoleusinate on rumen fermentation of kacang goats. Twelve buck kacang goats aged 12-14 months with initial body weight ranged 11-19 kg andthe average was 14,40 kg while 14,93% coefficient of variation was used in this reseach. Methode used was experiment methode with block randomized design as research design consist of four treatments and three replication. The treatmenten were T1 = mixed silage of sorghum-Clitoriaternatea providing, T1, T2 and T3 was T1 supplemen by concentrate with level of 10, 20 and 30 % containing of 150 mg ZnSO4 and 2% Zn-Cu Isoleusinat respectively. Parameter measured was rumen pH value, NH3 and total of VFA concentration. The data obtained was analyzed by analysis of variance (ANOVA) and followed by Least Significant Different test. The results of statistical analysis showed that supplementation with various levels of concentrates containing 150 mg ZnSO4 and 2% Zn-Cu Isoleucine had no significant effect (P> 0.05) on rumen pH and NH3 concentration, while significantly efect (P <0.05) on VFA totalt. It can be concluded that supplementation with various concentrates containing ZnSO4 and Zn-Cu Isoleucicate produced relatively the same pH and NH3 and VFA tended to increase, with the best concentration of concentrate supplementation at 30%.